فلسفة اللغة عند نعوم تشومسكي - عشبي, منال; عطالله, جهاد (جامعة الوادي - University of Eloued, 2023)
Through our study of Noam Chomsky's philosophy of the language, we have drawn several results, as follows: Chomsky introduced a new and additional theory that challenges previous theories in the American schools , called the Transformative-Generative Theory. This theory focuses on studying the structures of collective composition, meaning sentences, and considers the sentence as the central element of its studies. Chomsky also argued that language in humans is an innate characteristic. In our study of this theory, we noticed that language acqusition it requires comprehending the stages it went through and what each stage entails in terms of rules. To study This Theory, we hi light on: • Noam Chomsky's biography. • The Transformative-Generative Theory. • Its stages, principles, and some of its terms. الملخص: إن تشومسكي أضاف نظرية جديدة مقوضة لكل ما انتشر سابقاً في المدارس الأمريكية وهي النظرية التوليدية التحويلية القائمة على دراسة التراكيب جمع تركيب ويعني الجملة وهو تبنى الجملة وجعلها محور لدراساته في هذه النظرية، كما قامت كذلك على أن اللغة عند الإنسان ذات خاصية فطرية. من خلال دراستنا لهذه النظرية لاحظنا أنه لا يمكن فهم هذه النظرية إلا من خلال فهم المراحل التي مرت بها وكذا ما تتضمنه كل مرحلة من هذه المراحل من قواعد، ولدراسة هذه النظرية ألقيت الضوء على: 1: السيرة الذاتية لنعوم تشومسكي. 2: النظرية التوليدية التحويلية. 3: مراحلها ومبادئها وبعض مصطلحاتها.
مذكرة ماستر فلسفة
Keywords: عربيّــة:التوليد، التحويل، اللغة، التركيب، الملكة، البنية; generation, transformation, language, composition, structure, innate